Acute and sub-acute toxicity profile of crude extract and fractions of Gymnema sylvestre - Rofiyat Omolara Raji (Clinical Phytoscience, 2021)
Abstract Background Gymnema sylvestre is a reputable medicinal plant commonly explore for the management of diabetes and other ailments in traditional medicine. In the present study, we investigated the phytochemical compositions and effect of crude extract, hexane, and ethyl-acetate fractions of Gymnema sylvestre on biochemical and hematological parameters of Wistar rats. Methods Albino rats were distributed randomly into a control group and nine treatment groups orally administered crude extract and fractions of Gymnema sylvestre (100, 300, and 600 mg/kg BW) for 21 days. Liver and kidney function indices, as well as hematological parameters, were monitored. Results Our results revealed that the crude methanol extract contains flavonoids (8.56 ± 0.50 mg/g), alkaloids (13.84 ± 0.67 mg/g), total phenol (1.98 ± 0.50 mg/g), saponins (23.85 ± 0.35 mg/g) and tannins (16.00 ± 0.34 mg/g). The crude methanol, ethyl acetate and n-hexane fractions of Gymnema sylvestre had LD50 greater than 5000 mg/kg BW in acute oral toxicity test. The extract and fractions at 300 and 600 mg/kg BW cause loss of body weight of the rats, significantly altered (p < 0.05) the levels of biochemical indices including the aspartate transaminases, alanine transaminase, alkaline phosphates, bilirubin, proteins, urea, creatinine, and white blood cells (WBC) counts when compared with the non-treated control. However, the extract and fractions at 100 mg/kg BW did not cause any significant (p > 0.05) alterations to the levels of biochemical and hematological parameters when compared with the non-treated control. Conclusion Gymnema sylvestre at sub-acute doses of 300 and 600 mg/kg BW could compromise the functional integrity of the rats’ liver and kidney. The study, therefore, suggested the use of Gymnema sylvestre for oral remedy at a dose of 100 mg/kg or below.